Transforming Empire: The Ottomans from the Mediterranean to the Indian Ocean : Essays in Honor of Linda Darling - Atamaz, Serpil; İnal, Onur; Schweig, Alexander (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
This book places the Ottoman Empire within the global context and provides insight into the multifaceted transimperial and transnational connections that characterized it in different periods. It focuses on the connections, interactions, exchang